2018
DOI: 10.1039/c8dt01405a
|View full text |Cite
|
Sign up to set email alerts
|

Microporous 2D indium metal–organic frameworks for selective CO2 capture and their application in the catalytic CO2-cycloaddition of epoxides

Abstract: Four new 2D indium metal-organic frameworks (MOFs) (Me2NH2)[In(SBA)2] (1), (Me2NH2)[In(SBA)(BDC)] (2), (Me2NH2)[In(SBA)(BDC-NH2)] (3), and (NH4)3[In3Cl2(BPDC)5] (4), (H2SBA = 4,4'-sulfonyldibenzoic acid; H2BDC = 1,4-benzenedicarboxylic acid; H2BDC-NH2 = 2-amino-1,4-benzenedicarboxylic acid; H2BPDC = 4,4'-biphenyldicarboxylic acid) have been synthesized under solvothermal reaction conditions for compounds 1 to 3 and the DES (deep eutectic solvent) reaction has been attempted for compound 4. The structure of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 53 publications
0
31
0
Order By: Relevance
“…MOFs are frequently used as a filler for fabrication of a mixed matrix membrane due to the partial organic nature of its framework-affinity toward a polymeric matrix is higher than other purely inorganic materials. Two dimensional (MOF nanosheets) MOFs have been also reported to show favorable applications in catalysis [66,67], gas storage and separations [68,69], and chemical sensors [70,71]. MOF nanosheets are prepared in two different ways: 1) Bottom-up synthesis (c.f., arresting crystallization) [72], 2) Top-down synthesis (c.f., exfoliation of layered MOF crystals) [73,74] (Fig.…”
Section: Metal Organic Framework (Mof)mentioning
confidence: 99%
“…MOFs are frequently used as a filler for fabrication of a mixed matrix membrane due to the partial organic nature of its framework-affinity toward a polymeric matrix is higher than other purely inorganic materials. Two dimensional (MOF nanosheets) MOFs have been also reported to show favorable applications in catalysis [66,67], gas storage and separations [68,69], and chemical sensors [70,71]. MOF nanosheets are prepared in two different ways: 1) Bottom-up synthesis (c.f., arresting crystallization) [72], 2) Top-down synthesis (c.f., exfoliation of layered MOF crystals) [73,74] (Fig.…”
Section: Metal Organic Framework (Mof)mentioning
confidence: 99%
“…In another precedent, four 2D In MOFs, namely, (Me 2 NH 2 )[In(SBA) 2 ], (Me 2 NH 2 )[In(SBA)(BDC)], (Me 2 NH 2 )[In(SBA)(BDC‐NH 2 )], and (NH 4 ) 3 [In 3 Cl 2 (BPDC) 5 ] ( Figure ) (H 2 SBA:4,4′‐sulfonyldibenzoic acid; H 2 BDC‐NH 2 : 2‐amino‐1,4‐benzenedicarboxylic acid; H 2 BPDC: 4,4′‐biphenyldicarboxylic acid), were prepared under solvothermal reaction conditions . The powder XRD patterns of these 2D MOFs showed coincident diffraction patterns with their respective patterns simulated for their ideal structure, thus implying the phase purity of the bulk sample.…”
Section: Applications Of 2d Mofsmentioning
confidence: 99%
“…d) Thickness of the interpenetrated 2D framework structure of (NH 4 ) 3 [In 3 Cl 2 (BPDC) 5 ]. a–d) Reproduced with permission . Copyright 2018, Royal Society of Chemistry.…”
Section: Applications Of 2d Mofsmentioning
confidence: 99%
“…[16][17][18] Through literature research, we found that 4,4'-dicarboxybiphenyl sulfone (H 2 SDBA) as a Vshaped dicarboxylate ligand is an good candidate and has been widely employed as the organic building block for the construction of novel coordination frameworks independently or in combination with N-donor auxiliary ligands. [19][20][21][22][23] (2) and [Cu(SDBA) 0.5 (μ 2 -OH)] n (3) (H 2 SDBA=4,4'-dicarboxybiphenyl sulfone, im = imidazole, DMA = N,N'-dimethylacetamide). The structures of CPs 1-3 have been described, and the luminescent properties of 1-2, gas adsorption properties of 2 a (solvent-free form of 2) and photocatalytic property of 3 have also been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Among the reported CPs, polydentate organic carboxylic acid ligands have been proven to be one of the most effective organic building blocks to bind metal ions into well‐defined crystalline functional materials, [13–15] and lots of CPs with high thermal stabilities and promising functional properties have been synthesized by using the polycarboxylate ligands [16–18] . Through literature research, we found that 4,4’‐dicarboxybiphenyl sulfone (H 2 SDBA) as a V‐shaped dicarboxylate ligand is an good candidate and has been widely employed as the organic building block for the construction of novel coordination frameworks independently or in combination with N‐donor auxiliary ligands [19–23] . The characteristics of H 2 SDBA is the appropriate angle and spacer length between two coordination carboxylate groups.…”
Section: Introductionmentioning
confidence: 99%